Offshoring of white-collar services Business and economic perspective - Klimek, Artur (De Gruyter, 2020)
This is one of few books in the market dealing with offshoring of professional services, the dynamic phenomenon of high relevance in the global economy. The unique feature of the book is merging economic and business approaches to offshoring of professional services, so called offshoring of white-collar services. The work contains results of analysis of determinants and impacts on firm and economy levels.